Evaluation of Pollution Abatement Policies in the Marmara Sea with Water Quality Monitoring - BURAK, SELMIN (Asian Journal of Chemistry, 2010)
Istanbul Metropolitan area has been subjected to heavy population influx since 1950's and the non-existence of urban planning has aggravated the infrastructure problems by postponing effective measures. Rapid population growth on the one hand and industrialization on the other, have led to a soaring volume of domestic and industrial waste being discharged directly into the Marmara Sea and Istanbul Strait (Bosphorus). The assimilation capacity of the receiving waters, whose adverse hydrodynamic conditions are an important constraint, has been exceeded and pollution has damaged the natural ecological balance, eroding the range of beneficial uses for these waters. Consequently, the decline of the Marmara Sea reached an alarming level in the late 1970's. As a remedial action, comprehensive sewerage infrastructure investments have been initiated for Istanbul. This study discusses the achievement of the wastewater management program and obstacles encountered in the course of efforts to protect the marine environment of Istanbul based on representative results of the water quality monitoring study being carried out over the last ten years.